PERUBAHAN MOTIF KENDANGAN JAIPONG PADA PERTUNJUKAN WAYANG KULIT KI SENO NUGROHO - Asep Saepudin; Sigit Setiawan (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2019)
Acculturation of Sundanese and Javanese culture one of which appears in the Sundanese jaipong kendang motif that is adapted so that it becomes Javanese in character. This can be seen in the appearance of Wayang Kulit Ki Seno Nugroho. This study aims to analyze changes in kendang jaipong’s motives using the observation methode. Observation was carried out by revealing a systematic picture of the shadow puppet show, the player’s behavior, and paying attention to the space, place, actors, activities, time, and events. From the observation, it was found that there was a change in the jaipong drum construction on the improvisation, ayak-ayak patterns, various pangjadi motives, bukaan, mincid, ngala, and tepak ngeureunkeun. The results of this study concluded that althought the presentation of jaipong drums imitated the Sundanese style, the resulting motives were generally not Sundanese motifs. All jaipong kendang motifs are responded creatively to new motifs by Seno Nugroho drummer so that the results of their work are not Sundanese but Javanese.Keywords: tepak, jaipong, mincid, seno.